Empowerment of MSMEs during the covid-19 pandemic with information technology - Iswanto Suwarno; Nia Maharani Raharja; Ipin Prasojo; Omar Tanane (Peneliti Teknologi Teknik Indonesia, 2021)
Onion rambak (onion crackers) and rice karak (rice crackers) “Acha” is a home industry in Boyolali, specifically in Gumukrejo, Teras District, Boyolali Regency. Hazardous materials such as borax are not used in the ingredients that composed the karak and rambak sold by this home industry. Mrs. Sunarni, the owner, is assisted by her family in running the rambak and karak businesses. This business was started about ten years ago, but the business license had not been obtained. This company's NPWP business license was in the form of village’s group NPWP. The output was substantial, with 75-100 kg of onion rambak and 50 kg of rice karak produced. Businesses dropped in sales as people's purchasing power declined due to decreased income caused by the COVID-19 pandemic. Production could be increased by changing the packaging logo to one that was more eye-catching and easier for the public to remember. In addition to serving sales through the Whatsapp application, sales were also made through e-commerce applications such as Shopee. Using online sales through e-commerce applications, the production results and sales revenue for Mrs. Sunarni's rambak and karak businesses increased.